2017
DOI: 10.1371/journal.pone.0182027
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of endoplasmic reticulum- mitochondria interactions in beta cells from patients with type 2 diabetes

Abstract: Type 2 diabetes develops when beta cells are not able to fulfill insulin needs. The role of the endoplasmic reticulum–mitochondria junction in coordinating the functions of these two organelles throughout the natural history of type 2 diabetes is determinant and may explain the alterations of insulin biosynthesis. Our goal was to study endoplasmic reticulum and mitochondrial interactions in human beta cells from organ donors with type 2 diabetes. Pancreas samples were obtained via the network for pancreatic or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
67
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(71 citation statements)
references
References 31 publications
2
67
1
1
Order By: Relevance
“…The direct modulation of intracellular Ca 2+ release channels on the ER offers a novel mechanistic insight on the diabetogenic effect of sirolimus. Intriguingly, the upregulation of IP3R observed in pancreatic β cells following sirolimus treatment is consistent with the recent observation that IP3R levels are increased in islets from diabetic patients, mirrored by a reduced number of interactions between ER and mitochondria 64 . Additionally, Madec and colleagues had shown that exposing pancreatic islets to high glucose concentrations led to increased levels of IP3R 65 .…”
Section: Discussionsupporting
confidence: 90%
“…The direct modulation of intracellular Ca 2+ release channels on the ER offers a novel mechanistic insight on the diabetogenic effect of sirolimus. Intriguingly, the upregulation of IP3R observed in pancreatic β cells following sirolimus treatment is consistent with the recent observation that IP3R levels are increased in islets from diabetic patients, mirrored by a reduced number of interactions between ER and mitochondria 64 . Additionally, Madec and colleagues had shown that exposing pancreatic islets to high glucose concentrations led to increased levels of IP3R 65 .…”
Section: Discussionsupporting
confidence: 90%
“…This glucose-dependent regulation of ER-mitochondria MCSs is defective in the liver of insulin-resistant obese mice (Theurey et al, 2016), which show increased ER-mitochondria MCSs, causing mitochondrial dysfunction through mitochondrial Ca 2+ overload (Arruda et al, 2014). Pancreatic beta-cells from patients with type 2 diabetes show reduced ER-mitochondria MCSs, and a similar effect is observed after fatty acid overload (Thivolet et al, 2017). Interestingly, ER-mitochondria MCSs are reduced in pro-opiomelanocortin neurons of diabetic mice, and reduction of ER-mitochondria MCSs in the same neurons, via ablation of MFN2, induces leptin resistance and obesity (Schneeberger et al, 2013).…”
Section: Peripheral Neuropathies and Ermentioning
confidence: 99%
“…Studies in beta‐cells also indicate the existence of alterations in response to metabolic stress. Thivolet et al reported an increased IP3R2 and decreased VDAC1 expression, accompanied by reduced mitochondria–ER contact sites in beta‐cells from type 2 diabetic patients. In addition, Min6‐B1 beta‐cells exposed to palmitate show ER stress, reduced mitochondria–ER contacts, and impaired insulin secretion .…”
Section: Contacts Between Mitochondria and Other Organellesmentioning
confidence: 99%
“…Thivolet et al reported an increased IP3R2 and decreased VDAC1 expression, accompanied by reduced mitochondria–ER contact sites in beta‐cells from type 2 diabetic patients. In addition, Min6‐B1 beta‐cells exposed to palmitate show ER stress, reduced mitochondria–ER contacts, and impaired insulin secretion . Zhang et al reported increased VDAC1 abundance accompanied by mislocalization of part of VDAC1 to the plasma membrane.…”
Section: Contacts Between Mitochondria and Other Organellesmentioning
confidence: 99%